2016
DOI: 10.3390/su8010077
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Financial Sustainability for Farm Credit Applications—A Delphi Study

Abstract: Farmers use credit from commercial credit providers to finance production activities. Commercial credit providers have to predict the financial sustainability of the enterprise to ensure that the borrower will have the ability to repay the loan. A Delphi study was conducted to explore what factors are used as indicators of loan-repayment ability of farmers. The objective was not only to identify factors that are currently considered, but also to identify other personal attributes that may improve the accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 28 publications
1
46
0
Order By: Relevance
“…Also, the educational status of beneficiaries was found to have a positive influence on the payment and sustainability of agricultural credit schemes in Nigeria [79], and in other similar contexts [76,80,81]. However, this result contradicts a case in South Africa, in which education was observed as a less important variable in predicting the repayment ability and sustainability of credits [82].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the educational status of beneficiaries was found to have a positive influence on the payment and sustainability of agricultural credit schemes in Nigeria [79], and in other similar contexts [76,80,81]. However, this result contradicts a case in South Africa, in which education was observed as a less important variable in predicting the repayment ability and sustainability of credits [82].…”
Section: Discussionmentioning
confidence: 99%
“…In order to accomplish the purpose of this research, previous research was reviewed and summarized, and the Delphi method was used to develop the lifetime value index of casino customers. Studies related to the development of indicators in new fields were conducted through intuition and consensus of experts through the Delphi method [27,28].…”
Section: Procedures Of Studymentioning
confidence: 99%
“…International efforts were made to supply agriculture with financial resources [36][37][38]. For example, the Farm Credit System of the USA, was used as a last resort financing source [18,39] which was created especially for the risky agricultural activities, its result being the development of the rural areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[13] The study reveals that small farms are less likely to receive a credit and are more exposed to loss. [38] The findings of the Auto-Regressive Distributed Lag approach showed that short and long run relationship exist between agricultural credit and economic growth in both short and long run in Nigeria. Economic growth is influenced by dynamic variables, such as credit to agricultural sector, real exchange rate, real interest rate, private domestic investment and inflation rate.…”
Section: Main Findings Referencementioning
confidence: 99%